2008
DOI: 10.1136/ard.2007.077974
|View full text |Cite
|
Sign up to set email alerts
|

A high incidence of disease flares in an open pilot study of infliximab in patients with refractory inflammatory myopathies

Abstract: Infliximab treatment was not effective in refractory inflammatory myopathies. In view of radiological and clinical worsening, and activation of the type I IFN system in several cases, infliximab is not an alternative treatment in patients with treatment-resistant myositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
1
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(155 citation statements)
references
References 38 publications
2
143
1
9
Order By: Relevance
“…There is also evidence that blockage of TNF-α causes exacerbation or prolongation of preexisting autoimmune diseases such as multiple sclerosis in humans and mice 10 . In accord with our findings, Dastmalchi, et al documented a worsening of muscle inflammation during infliximab therapy in patients with DM and polymyositis 11 .…”
Section: To the Editorsupporting
confidence: 82%
“…There is also evidence that blockage of TNF-α causes exacerbation or prolongation of preexisting autoimmune diseases such as multiple sclerosis in humans and mice 10 . In accord with our findings, Dastmalchi, et al documented a worsening of muscle inflammation during infliximab therapy in patients with DM and polymyositis 11 .…”
Section: To the Editorsupporting
confidence: 82%
“…Although the Muscle Study Group demonstrated disease improvement in nearly half of the patients receiving etanercept for adult DM, 5 patients developed a worsening rash while receiving this treatment (8). An open-label study of infliximab in 13 adults with refractory idiopathic inflammatory myopathy demonstrated poor improvement (15). In fact, of the 9 patients who completed this open-label study, at followup, 5 patients demonstrated muscle inflammation by magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…An open-label study looking at the efficacy of infliximab combined with methotrexate was terminated owing to a low inclusion rate and a high dropout rate due to disease progression or side effects [91]. Another open-label study of infliximab performed in 13 patients with refractory DM/PM/IBM found no patients improved in muscle strength, measured by manual muscle testing, and several patients actually worsened [92]. A study of etanercept in active DM did not show any initial improvement until an additional drug (methotrexate or azathioprine) was added [93].…”
Section: Cytokine-based Therapiesmentioning
confidence: 99%